2008
DOI: 10.1063/1.2883937
|View full text |Cite
|
Sign up to set email alerts
|

Settling of an isolated spherical particle in a yield stress shear thinning fluid

Abstract: We visualize the flow induced by an isolated non-Brownian spherical particle settling in a shear thinning yield stress fluid using particle image velocimetry. With ReϽ 1, we show a breaking of the fore-aft symmetry and relate this to the rheological properties of the fluid. We find that the shape of the yield surface approximates that of an ovoid spheroid with its major axis approximately five times greater than the radius of the particle. The disagreement of our experimental findings with previous numerical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
110
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 35 publications
7
110
0
4
Order By: Relevance
“…Atapattu et al [1], for example, tried to determine the approximate shape of the sheared zone around a sphere in a Carbopol gel on the basis of experimentally determined velocity profiles. More recently, Putz et al [4,5] re-examined the case of a sphere settling in the same type of gel. Tokpavi et al [6,7] examined that of a cylinder in a very slow flow.…”
Section: Introductionmentioning
confidence: 96%
“…Atapattu et al [1], for example, tried to determine the approximate shape of the sheared zone around a sphere in a Carbopol gel on the basis of experimentally determined velocity profiles. More recently, Putz et al [4,5] re-examined the case of a sphere settling in the same type of gel. Tokpavi et al [6,7] examined that of a cylinder in a very slow flow.…”
Section: Introductionmentioning
confidence: 96%
“…Gueslin et al [26] provided an in-depth study of the velocity field but this concerned a thixotropic material for which there can be a further, and maybe dramatic, impact of the intense shear rate close to the object surface. Finally some works [27,28] (for spheres) and [24] (for cylinders) provided new detailed data concerning the velocity field around an object moving through a yield stress fluid. They found a significant discrepancy of the velocity field with that computed from simulations.…”
Section: Introductionmentioning
confidence: 99%
“…It has only recently been found that within this framework, one cannot properly describe some of the ''simplest'' fluid dynamics phenomena such as the flow pattern in the wake of a spherical object uniformly moving through a Carbopol Ò gel Putz et al [40], the flow pattern in the wake of a cylinder Tokpavi et al [45] or the slow oscillatory pipe flow Carbopol Ò gel, Park and Liu [34]. The measurements presented in these references indicate the presence of several rheological features somewhat incompatible with the classical ''model yield stress fluids'' picture of Carbopol Ò gels: pronounced elastic effects in the vicinity of the yield point, time dependence and irreversibility of the deformation states.…”
Section: Introductionmentioning
confidence: 99%